Network analysis of central symptoms in Chinese young adults with subthreshold depression - Xiumin Jiang; Xiaotong Wang; Lin Yu; Jun He; Shengwei Wu; Yuanyuan Zhou; Meng Zhang; Lin Yao; Jinglan Yan; Yuanjia Zheng; Yongjun Chen (Translational Psychiatry)
Abstract Subthreshold depression (SD) is a prevalent condition among young adults, significantly increasing the risk of developing major depressive disorder (MDD). While the symptoms of MDD are well-documented, the network structure and key symptoms of SD, which forms a complex, interdependent system, have not been fully elucidated. This study sought to identify the central symptoms and their interconnections within the depressive symptom network in young adults with SD. A total of 834 Chinese young adults with SD completed the 21-item Beck Depression Inventory 2nd version (BDI-II) and were included in this study. Network analysis was employed to identify central symptoms (nodes) and associations between symptoms (edges) as assessed by the BDI-II. Additionally, centrality indicators for network robustness underwent assessment through stability and accuracy tests. The analysis revealed that Loss of interest was the most central node in the SD symptom network, with Tiredness/fatigue and Agitation following closely. Significant associations were observed between Loss of energy and Concentration difficulties, Agitation and Irritability, Guilty feelings and Self-dislike, as well as Tiredness and Loss of pleasure. The network demonstrated robustness across stability and accuracy assessments. Loss of interest, Tiredness/fatigue, and Agitation were pivotal symptoms within the depressive symptom network of SD in young adults. These symptoms may serve as critical targets for therapeutic interventions and should be prioritized in future psychological and neurobiological research to advance our understanding of SD.